Gerakan Pemasangan Biopori Untuk Pura Di Denpasar (Gempar) Sebagai Wujud Program Ekoteologi Hindu Versi KMHDI - Darma Permana, I Dewa Gede (Satya Widya: Jurnal Studi Agama, 2024)
Abstract The problem of waste after Hindu ceremonies in Bali has been highlighted. This made PC KMHDI Denpasar create a work program called "Biopori Installation Movement for Temples in Denpasar" (GEMPAR). Based on these problems, this research tries to examine more holistically the essence of the presence of GEMPAR as a work program based on Hindu Ecotheology. In order to support the purpose of this research, 3 problem formulations were formulated, including: 1) The nature of biopori as an environmentally friendly technology, 2) Tri Hita Karana as a Hindu Ecotheology guideline, and 3) The essence of the GEMPAR is a form of Hindu Ecotheology program from KMHDI. Through a qualitative type of research method that uses a case study approach, the results of this study describe the results and discussion that: 1) Biopori is an innovative technology that can play a role in ceremonial waste management in the temple environment. 2) Tri Hita Karana is a Hindu Ecotheology guideline that acts as a reference in maintaining harmony between humans with God, humans with fellow humans, and humans with the surrounding environment. 3) GEMPAR is a form of Hindu Ecotheology program from KMHDI which has useful implications for preserving nature and its contents.